2006
DOI: 10.1037/1091-7527.24.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned: Challenges implementing a personal digital assistant (PDA) to assess behavioral health in primary care.

Abstract: Multiple barriers to optimal behavioral health care in primary care settings exist, yet it continues to be the treatment setting of choice for most people with behavioral health conditions. This article describes some of these barriers and how information technology may address them. The authors discuss their experiences implementing a computerized behavioral health assessment in four urban primary care clinics, the lessons they learned that warrant attention before successful implementation is possible, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Overall, eight studies identified barriers to coordinated care 18 25 ( Table 1 ), and 13 studies 9 , 12 , 16 , 26 – 35 ( Table 2 ) did not specifically mention challenges facing care coordination, five of which 9 , 12 , 18 , 34 , 35 were specifically designed to compare the collaborative care model to CAU ( Table 2 ). Mental health illnesses addressed in the reviewed articles included dementia (n=2), 18 , 27 suicide (n=1), 28 substance abuse (n=4), 22 , 24 , 28 , 31 posttraumatic stress disorder (PTSD; n=2), 32 , 33 schizophrenia (n=1), 32 anxiety (n=1), 35 and depression, the most prevalent mental health condition assessed for collaborative care (n=9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, eight studies identified barriers to coordinated care 18 25 ( Table 1 ), and 13 studies 9 , 12 , 16 , 26 – 35 ( Table 2 ) did not specifically mention challenges facing care coordination, five of which 9 , 12 , 18 , 34 , 35 were specifically designed to compare the collaborative care model to CAU ( Table 2 ). Mental health illnesses addressed in the reviewed articles included dementia (n=2), 18 , 27 suicide (n=1), 28 substance abuse (n=4), 22 , 24 , 28 , 31 posttraumatic stress disorder (PTSD; n=2), 32 , 33 schizophrenia (n=1), 32 anxiety (n=1), 35 and depression, the most prevalent mental health condition assessed for collaborative care (n=9).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies used health information technologies to coordinate care among patients and providers, including computer cognitive behavior therapy, 35 agent-based simulation modeling, 16 density mapping technology, 27 telemedicine, 12 , 26 , 32 , 33 and Internet Web-based communication. 9 , 18 , 20 , 24 , 25 EHRs were the most common health information technology used. 12 , 18 , 19 , 21 23 , 26 , 29 , 30 A single study used the Aging Brain Care Medical Home model to facilitate care coordination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research may benefit from assessing whether similar results can be achieved when substituting smartphones for PDAs. Researchers have also noted technical difficulties associated with PDA integration, such as PDA crashes, participants forgetting identification codes and passwords, and differing software systems between the devices and linked desktop computers (Yon, Johnson, Harvey-Berino, Gold, & Howard, 2007;Zeman, Johnson, Arfken, Smith, & Opoku, 2006), many of which may be overcome through using smartphones for similar functions.…”
Section: Current Research Limitations and Future Directionsmentioning
confidence: 99%